2017
DOI: 10.1016/j.prrv.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Child pneumonia – focus on the Western Pacific Region

Abstract: Worldwide, pneumonia is the leading cause of death in infants and young children (aged <5 years). We provide an overview of the global pneumonia disease burden, as well as the aetiology and management practices in different parts of the world, with a specific focus on the WHO Western Pacific Region. In 2011, the Western Pacific region had an estimated 0.11 pneumonia episodes per child-year with 61,900 pneumonia-related deaths in children less than 5 years of age. The majority (>75%) of pneumonia deaths occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 81 publications
0
41
0
6
Order By: Relevance
“…Correspondingly, a study in Ghana also indicated that 99% of the households use biomass as their primary fuel source [35] and according to the global solid-fuel use estimation, 2.8 billion people still burn solid fuels for cooking [36]. However, HAP exposure from cooking with biomass fuels has been linked with childhood pneumonia [37,38] and an up to date estimate of the disease burden of HAP suggests that every year, HAP from biomass fuel use causes 455,000 ALRI deaths and an ALRI population attributable fraction of 52% globally [39]. The use of unclean fuel for household cooking was also found to elevate the odds of childhood ARI in South Ethiopia with an AOR of 2.09 (95% CI: 1.03-4.22) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, a study in Ghana also indicated that 99% of the households use biomass as their primary fuel source [35] and according to the global solid-fuel use estimation, 2.8 billion people still burn solid fuels for cooking [36]. However, HAP exposure from cooking with biomass fuels has been linked with childhood pneumonia [37,38] and an up to date estimate of the disease burden of HAP suggests that every year, HAP from biomass fuel use causes 455,000 ALRI deaths and an ALRI population attributable fraction of 52% globally [39]. The use of unclean fuel for household cooking was also found to elevate the odds of childhood ARI in South Ethiopia with an AOR of 2.09 (95% CI: 1.03-4.22) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia, acute respiratory infection caused by bacterial pathogens such as Haemophilus influenzae, Streptococcus pneumoniae, and Staphylococcus aureus, is one of the leading causes of morbidity and mortality in developing countries, including the Philippines. The majority of severe episodes occurs in children under five years, the elderly and immuno-compromised individuals [1]. A timely antibiotic therapy can reduce its fatal cases; nevertheless, access to the health services is the most important health problem in the Philippines [2a].…”
mentioning
confidence: 99%
“…Correspondingly, a study in Ghana also indicated that 99% of the households use biomass as their primary fuel source (35) and according to the global solid-fuel use estimation, 2.8 billion people still burn solid fuels for cooking (36). However, HAP exposure from cooking with biomass fuels has been linked with childhood pneumonia (37,38) and an up to date estimate of disease burden of HAP suggests that every year, HAP from biomass fuel use causes 455 000 ALRI deaths and an ALRI population attributable fraction of 52% globally (39). The use of unclean fuel for household cooking was also found to elevate the odds of childhood ARI in South Ethiopia with an AOR of 2.09 (95% CI:…”
Section: Discussionmentioning
confidence: 99%